Socio-economic transformation follows environmental change on Svalbard - Węsławski, Jan Marcin; Urbański, Jacek; Piwowarczyk, Joanna; Cochrane, Sabine K.J.; Søreide, Janne (Polish Polar Research, 2025)
The European Arctic, which includes the Svalbard archipelago, is situated in one of the areas showing most notable changes due to global warming and associated cascade events and processes. The main driving factor, temperature rise, is continuing to cause a large-scale overall decline in ice, from glacier retreating, less coastal land-fast ice to thinning and shrinking of open-sea pack ice. This, together with increased inflow of Atlantic waters, is causing profound changes in the local fauna, food web and biodiversity. In parallel, changes in landscape are also notable, mainly due to increasing coastal erosion and glacial melt. Over the past decades, both the traditional hunting-trapping lifestyle and mining have declined almost to the point of non-existence. At the same time, destination tourism and scientific research have become the major industries, both associated with an increase in the size of the main settlement of Longyearbyen, and thus also service jobs and local administration. Along with the shrinking of the glaciated Arctic landscape, the archipelago exemplifies the broadest level of nature protection in Europe. Strict environmental regulations that restrict and even prohibit human activities in large areas contribute to Svalbard being one of the best formally protected wilderness environments in the entire Arctic. Thus, as Svalbard marine ecosystems continue to change, they also are becoming more accessible to humans, and so also anthropogenic pressures are both changing and increasing in extent. We provide a compilation of both ecosystem components and human activities, together with indications of how these are, in parallel, changing. This forms the basis for future ecosystem and societal valuation assessments.